A One Health-based Conceptual Framework for comprehensive and coordinated prevention and preparedness to health threats. (March 2022) - Dente, M.G.; Riccardo, F.; Milano, A.; Robbiati, C.; Agrimi, U.; Morabito, S.; Carere, M.; Marcheggiani, S.; Mantovani, A.; Mancini, L.; Villa, L.; Monaco, M.; et al.
Abstract : Purpose: Prevention and preparedness to health threats pose several challenges: to identify multifactorial drivers, to detect and evaluate risks as early as possible, to involve multiple actors and stakeholders and to make information and data transversely and transparently accessible. One Health (OH) can provide a strategic scientific support if OH strategies are integrated in prevention and preparedness plans at national and international level and OH-based Conceptual Frameworks (OHCF) could facilitate this integration. Methods & Materials: We conducted a scoping review to identify aspects in existing prevention and preparedness plans that could benefit of OH strategies and developed a OH based Conceptual Framework (OHCF). Results: Enhancing prevention and early detection capacity to reduce the societal costs of a pandemic, considering integrated drivers for epidemic/pandemic preparedness, involving the multiplicity of the actors, stakeholders, disciplines and related interests, ensuring prompt access and share of information and data are among the priorities to address which could be supported by One Health strategies. A OHCF has been developed with a multidisciplinary effort to facilitate detection of threats at the human-animal-environment interface, assess risks for pandemic, support evaluation of possible impacts and provide input for prevention. The OHCF aims at guiding the relevant national sectors towards harmonised and context driven OH strategies in prevention and preparedness and identifies priority actions for Governance, Data collection and analysis and Capacity building, both at national and international level. Conclusion: At present, stand-alone national One Health plans are often developed, while the effort, in order to benefit from One Health approaches, should be to appropriately integrate One Health strategies into relevant national and international plans. It is therefore necessary to develop adequate frameworks and identify procedures that allow this integration and effective implementation of comprehensive prevention and preparedness strategies. The adoption of the proposed OHCF would facilitate the development of intersectoral data sharing and analysis platforms and support decision-making based on early signals which contemplate possible uncertainties. The OHCF will facilitate operationalisation of OH in prevention and preparedness and will guide assessment of the multiple potential risk factors involved before they became a threat.